Geography and the environment in Southeast Asia : proceedings of the Department of Geography and Geology Jubilee Symposium, University of Hong Kong, 21-25 June, 1976 - Hill, R. D. (Ronald David), 1935-; Bray, Jennifer M. (Published by the Hong Kong University Press for the Dept. of Geography and Geology, University of Hong Kong, 1978)
Over 30 participants from 10 countries attended the Symposium and this is a collection of their submitted papers, rearranged into five sections, focusing on problems of the urban environment, on the impact of the city on surrounding rural areas and of socio-economic development in general on the rural environment, on available tools for analysis and planning, and on the goals and methods of environmental education in its broadest sense. the views expressed in these papers will be useful and of interest to both students and research workers in the fields of human geography and other related dis.